2016
DOI: 10.1213/ane.0000000000001189
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Oxygen Insufflation During AirTraq Laryngoscopy Slows Arterial Desaturation in Infants and Small Children

Abstract: Adding posterior pharyngeal oxygen insufflation to conventional preoxygenation prolonged the period of adequate oxygen saturation in infants and small children by an amount that is potentially clinically important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 10 publications
0
30
1
Order By: Relevance
“…Apnoeic oxygenation can be achieved with any device that enables administration of oxygen into the respiratory tract, including facemask, nasal cannula, nasopharyngeal catheter, supraglottic airway device, rigid bronchoscope, tracheal tube and front‐of‐neck catheter. Oxygen insufflation can also occur through channels located in direct and videolaryngoscopes .…”
Section: High‐flow Nasal Oxygen: Novel Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apnoeic oxygenation can be achieved with any device that enables administration of oxygen into the respiratory tract, including facemask, nasal cannula, nasopharyngeal catheter, supraglottic airway device, rigid bronchoscope, tracheal tube and front‐of‐neck catheter. Oxygen insufflation can also occur through channels located in direct and videolaryngoscopes .…”
Section: High‐flow Nasal Oxygen: Novel Mechanismsmentioning
confidence: 99%
“…Randomised controlled trials have shown a delayed time to oxygen desaturation with use of pharyngeal oxygen insufflation during elective traxcheal intubation . In one study, apnoeic oxygenation with high‐flow nasal oxygen at 1–2 l.kg.min −1 reduced the incidence of desaturation during intubation when compared with a control arm that did not receive any supplemental oxygen during apnoea .…”
Section: Paediatricsmentioning
confidence: 99%
“…A recent case report demonstrated the utility of apneic oxygenation with low flow nasal cannula in a premature dysmorphic neonate who tolerated three intubation attempts without hypoxemia or bradycardia . Randomized trials in pediatric patients have shown that deep pharyngeal or laryngeal insufflation of oxygen via a laryngoscope results in slower rate of oxygen desaturation during laryngoscopy and extends apneic time before the onset of hypoxemia . In addition to the above techniques, the use of high flow, humidified oxygen via nasal cannula, as well as via simple nasal cannula at rates as low as 0.2 L/kg/min, has been shown to extend safe apneic times in pediatric patients and is reviewed by Humphreys and Schibler elsewhere in this issue.…”
Section: Oxygen Deliverymentioning
confidence: 99%
“…Both prolong safe apnoea time. In paediatric practice, pharyngeal oxygen delivered via the laryngoscope is a well‐established technique, and this might also have utility in the adult population .…”
Section: Avoiding Hypoxiamentioning
confidence: 99%